2007
DOI: 10.1300/j013v45n04_01
|View full text |Cite
|
Sign up to set email alerts
|

Self-Rated Health and Postnatal Depressive Symptoms Among Immigrant Mothers in Québec

Abstract: Data from the Québec Longitudinal Study of Child Development were used to examine factors associated with postnatal depression and the links between self-rated health (SRH) and depressive symptoms in mothers 5 months after giving birth, according to immigration status. Postnatal depressive symptoms were measured using the 12-item Center for Epidemiologic Studies Depression Scale (CES-D). Immigrant mothers were classified according to their ethnocultural (majority or minority) group and compared with Canadian-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 35 publications
4
60
1
1
Order By: Relevance
“…20,21 For example, some studies in specific Canadian cities report greater incidence rates of mental health disorders among migrant populations. 20,22 The contradictory and equivocal findings of studies concerned with migrants' mental health make it relevant to analyze a broader range of available national data.…”
mentioning
confidence: 99%
“…20,21 For example, some studies in specific Canadian cities report greater incidence rates of mental health disorders among migrant populations. 20,22 The contradictory and equivocal findings of studies concerned with migrants' mental health make it relevant to analyze a broader range of available national data.…”
mentioning
confidence: 99%
“…A study of new mothers in Sweden found factors associated with poor self-rated health included tiredness, musculoskeletal problems, abdominal pain, emotional problems, depression, negative experiences of breast feeding, infant sleeping problems, prematurity and poor social support [39]. Postnatal depression has previously been found to be associated with poor self-rated health [40]. It is also possible that poor self-rated health is related to the feeling of “loss of control” and to birth-related trauma and stress.…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that having unmet needs may contribute to the greater risk for migrants/minorities to develop postpartum depression (Mechakra-Tahiri, Zunzunegui, & Seguin, 2007;Stewart, Gagnon, Saucier, Wahoush, & Dougherty, 2008). Whereas self-rated health was strongly associated with depressive symptoms in Canadian-born mothers (OR 3.46, 95% CI 2.54-4.72), there was no significant associations for minority immigrant mothers, suggesting that factors other than perceived health may be influential on depressive symptoms or that health is being evaluated around physical concepts (Mechakra-Tahiri et al, 2007).…”
Section: Downloaded By [Mcmaster University] At 11:35 04 November 2014mentioning
confidence: 99%